PENGARUH KEBIJAKAN HUTANG, KEPUTUSAN INVESTASI DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2014 – 2018 - MARDIAH HASANAH NASUTION (JURNAL ILMIAH KOHESI, 2021)
The purpose of this study is to determine the effect of debt policy (DER), investment decision (PER), and dividend policy(DPR) partially and simultaneously to the value of company. The study focused on manufacture companies listed onIndonesia Stock Exchange for the period of 2014-2018. The study used purposive sampling method in order to collect thesample. Population in this study are all manufacture companies that have been and are still listed in Indonesia StockExchange during period of 2014-2018. Based on certain criteria, there are 16 of 163 manufacture companies that matchedwith the sample with a 5 years observation (2014-2018). The statistical data were analyzed using multiple linear regressionmethod. The result of this study concluded that debt policy (DER) had a negative and significant effect on the value ofcompany with a t value of -3,255 and a significance of 0,002, as of the first hypothesis was accepted. Investment decision(PER) has a positive with a t value of 7,504 and a significance of 0,000 to the value of company, as of the second hypothesiswas accepted. Dividend policy (DPR) does not affect the value of company with a t value of 1,838 and a significance of 0,070,and so the third hypothesis was rejected. The results of model suitability test show that debt policy (DER), investmentdecision (PER), and dividend policy (DPR) simultaneously affect the value of company. This was indicated by a F value of31,341 and a significance of 0,000. The coefficient value of determination (Adjusted R2) of 0,541 show that the effect of debtpolicy (DER), investment decision (PER), and dividend policy (DPR) to the value of company is 54,2% and the remainingpercentage could be explained by other variables not examined in this study.